Impact of implementing respiratory point-of-care testing in a regional haemato-oncology unit. Issue 1 (September 2020) - Goldstein, E.J.; Dhillon, R.; McCullough, C.; Inkster, T.; Soutar, R.; Gunson, R.N.
Summary: Respiratory point-of-care testing (POCT) for the detection of influenza A, influenza B and respiratory syncytial virus (RSV) was implemented in response to recent RSV outbreaks at a regional haemato-oncology unit in Glasgow. This descriptive study, undertaken pre- and post-POCT implementation, suggests that POCT reduces the time taken to receive results and increases diagnostic rates in outpatients. It is likely that the reduction in turnaround time afforded by POCT also leads to a faster time to antiviral treatment, prompt isolation and a reduction in the number of hospital-acquired infections.